2020
DOI: 10.1109/ojemb.2020.3002447
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Regions At Risk for Spreading COVID-19 Using Existing Cellular Wireless Network Functionalities

Abstract: The purpose of this article is to introduce a new strategy to identify areas with high human density and mobility, which are at risk for spreading COVID-19. Crowded regions with actively moving people (called at-risk regions) are susceptible to spreading the disease, especially if they contain asymptomatic infected people together with healthy people. Methods: Our scheme identifies at-risk regions using existing cellular network functionalities-handover and cell (re)selection-used to maintain seamless coverage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 7 publications
0
42
0
Order By: Relevance
“…Many engineers, technicians, researchers, and scientists from our Society have participated in this fight (e.g., [1]- [8]). The developed technologies have addressed, for instance, the diagnosis of the disease [9]- [12]; identification and tracking of infected people and regions [13]; remote monitoring of patients; isolated, hospitalized patients' communication with people outside of the hospital; controlling the spread of disease [14]; and modeling of COVID-19 time-series data [15]. Novel solutions have been examined specifically to cope with the problems triggered by COVID-19.…”
Section: The Topicmentioning
confidence: 99%
“…Many engineers, technicians, researchers, and scientists from our Society have participated in this fight (e.g., [1]- [8]). The developed technologies have addressed, for instance, the diagnosis of the disease [9]- [12]; identification and tracking of infected people and regions [13]; remote monitoring of patients; isolated, hospitalized patients' communication with people outside of the hospital; controlling the spread of disease [14]; and modeling of COVID-19 time-series data [15]. Novel solutions have been examined specifically to cope with the problems triggered by COVID-19.…”
Section: The Topicmentioning
confidence: 99%
“…Furthermore, cellular phone network functionalities could provide the means to identify hotspots (e.g. crowded areas in skilled nursing facilities and food processing plants [11]). Smartphone applications for digital contact tracing could be used to monitor the population in regions at risk for an outbreak and identify as well as isolate COVID-19 cases and those who may have been exposed [12].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in the community, early detection of COVID-19 cases could be achieved by building upon prior studies which showed that by using wearable sensors to capture resting heart rate and sleep duration it is possible to predict influenza-like illness rates [9] as well as COVID-19 epidemic trends [10] . Furthermore, cellular phone network functionalities could provide the means to identify hotspots (e.g., crowded areas in skilled nursing facilities and food processing plants [11] ). Smartphone applications for digital contact tracing could be used to monitor the population in regions at risk for an outbreak and identify as well as isolate COVID-19 cases and those who may have been exposed [12] .…”
Section: Introductionmentioning
confidence: 99%
“…It alerts them immediately if they come closer than the required distance [13]. Some countries have adopted ubiquitous technologies, such as Wi-fi, cellular, GNSS positioning (localization) systems to monitor and alert the social distance in public and crowded areas [14], [1]. Recently, many countries worldwide have used the drones, IoT, and AIassisted techniques to monitor the human density, predict and alert the safe distance breach in crowded areas in indoor and outdoor [3].…”
Section: Introductionmentioning
confidence: 99%